Revision of the genus Typhlocybella Baker, 1903 (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) and description of a new species from Argentina - Catalano, María Inés; Paradell, Susana Liria; de Remes Lenicov, Ana María Marino (Zootaxa, 2012)
The dikraneurine leafhopper genus Typhlocybella Baker is revised based on a comparative morphological study, and a keyfor identification of males is provided. Five valid species are recognized, four of which were previously described and another one new, Typhlocybella affinis sp. nov. Typhlocybella parva Ruppel & DeLong is re-described.